From Suspended to Emergent Woman, An African American Criticism of Zora Neale Hurston’s Their Eyes Were Watching God - Simon Ntamwana (Rubikon : Journal of Transnational American Studies, 2017)
This paper discusses the rise of the woman from a downtrodden woman to an emergent subject through an assimilated subjugated woman in Zora Neale Hurston’s Their Eyes Were Watching God. It is based on the African American approach and Mary Helen Washington’s theory of black woman character types in African American literature.  It aims at identifying the woman character types in the novel and discussing the woman’s ascension from her patriarchal suspension into her emergence as an independent woman. Anchored on the hypothetical contention that the woman arises from suspension to emergence through assimilation phases, it was found out that during her gradual ascension and independence quest the woman subverts the oppressive patriarchy and its abusive masculinity and transforms it into a man equitably collaborating with her. Janie the protagonist born subservient to patriarchy like her grandmother Nannie fights to liberate herself through love and marriage. While the first marriage with Logan maintains her under patriarchal oppression, the second spousal union with Jody is a simulation of liberation that refrains her from public life and expression. Through gradual revolt against patriarchy, Janie reaches her desired woman selfhood in the third marriage with Tea Cake. Keywords: Suspended, Assimilated, Emergent, African American Literary Approach